Pengelolaan Personal Branding Gamaliel Tapiheru Melalui Media Sosial Instagram - Saragih, Elvan Adventri (Prisani Cendekia Institute, 2024)
Personal Branding is the way people shape themselves as they want to be seen by others. Gamaliel is a musician who made his debut as a professional musician with his music group